University reputation, support, and security: explaining changes in educational tourism and economic benefits - Omonova, Nilufar; Juraev, Abror; Makhmudova, Nodira; Utevskaia, Marina; Zhanabay, Aibek (Frontiers in Sustainable Tourism, 2025)
Educational tourism has become a key driver of economic growth in host countries, yet empirical evidence on its determinants remains fragmented. This study contributes to the literature by developing a comprehensive panel data model that integrates both economic (inflation rate, GDP per capita, tuition fees) and institutional (university rankings, student safety) factors to explain international student mobility. Using a dataset of 50 countries for the period 2019–2023 and applying fixed and random effects regression models, the analysis shows that university reputation (β2 = 0.673) is the most influential factor, followed by GDP per capita and safety infrastructure, while tuition fees have a significantly negative impact. The findings expand on previous studies by combining multi-country panel data with forecasting methods to project educational tourism flows for 2025–2028. The results confirm the multiplier effect of educational tourism through export revenues, infrastructure development, and human capital formation. This provides policymakers, particularly in emerging economies like Uzbekistan, with practical evidence for developing targeted strategies that enhance international competitiveness in higher education.